A randomised trial comparing weight loss with aerobic exercise in overweight individuals with coronary artery disease: The CUT-IT trial. (August 2015) - Pedersen, Lene R; Olsen, Rasmus H; Jürs, Anders; Astrup, Arne; Chabanova, Elizaveta; Simonsen, Lene; Wisløff, Ulrik; Haugaard, Steen B; Prescott, Eva
Background: We aimed to compare the effect of aerobic interval training (AIT) versus a low energy diet (LED) on physical fitness, body composition, cardiovascular risk factors and symptoms in overweight individuals with coronary artery disease (CAD). Methods and design: Seventy non-diabetic participants with CAD, a BMI>28 kg/m 2 and aged 45 to 75 years were randomised to 12 weeks' AIT at 90% peak heart rate three times a week or LED (800–1000 kcal/day) for 8–10 weeks followed by 2–4 weeks' weight maintenance diet. Results: Twenty-six (74%) AIT and 29 (83%) LED participants completed intervention per protocol. VO2 peak (mL/kg fat free mass 0.67 /min) increased by 10.4% ( p  = 0.002) following AIT, whereas no change was observed after LED (−3.0%, p  = 0.095). The LED group lost 10.6% body weight and 26.6% body fat mass ( p  < 0.001) compared to 1.6% ( p  = 0.002) and 5.5% ( p  < 0.001) following AIT. Waist circumference and visceral abdominal fat were reduced by both interventions but were most pronounced following LED (between-group, p  < 0.001). Total cholesterol, non-HDL-C and triglycerides decreased significantly in both groups whereas HDL-C and blood pressure were unchanged. Six participants had their antihypertensive treatment reduced following LED (between-group, p  = 0.032). Canadian Cardiovascular Society (CCS), New York Heart Association (NYHA) and anxiety scores were improved, while depressive symptoms remained unchanged. Intention-to-treat analyses including 65 participants (93%) were similar to per protocol analysis. Conclusion: Both interventions were feasible and effective in achieving the desired effects. LED was superior in improving body composition and blood pressure, whereas effects on lipids and symptoms were similar in the two groups. Thus, both AIT and LED improve the cardiovascular risk profile in overweight individuals with contemporarily treated CAD.